Autonomy Support in Finnish Schools - Xu, Ting (fi=Turun yliopisto|en=University of Turku|, 2016)
This thesis study of “Autonomy support in Finnish schools” was to reveal how Finnish teachers promote students’ autonomy in classroom activities. The concern of this study was the shift from the introjected regulation to the more autonomous regulation. Teacher-student relationships were supposed to contribute to this shifting. This study is empirical research under the framework of Self-Determination Theory. This study collected data via classroom observation and post-observation interviews. Data analysis was conducted in the coding-clustering-conceptualizing sequence simultaneously with the verification of existing internalization theory. The study found that teachers’ educational love with consistency, together with sustainable assessment could be the pivot for student to shift from validation-seeking to growth-seeking orientation. Self-regulation skills could facilitate the transfer of responsibility in scaffolding, which is vital for cognitive autonomy-support. The non-judgmental atmosphere in classroom and students’ argumentative skills were identified as possible factors to contribute to social regulation in cooperative learning and collaborative learning activities.